2015
DOI: 10.1186/s12906-015-0520-z
|View full text |Cite
|
Sign up to set email alerts
|

Arthropod steroid hormone (20-Hydroxyecdysone) suppresses IL-1β- induced catabolic gene expression in cartilage

Abstract: BackgroundIn osteoarthritis (OA), the imbalance of chondrocytes’ anabolic and catabolic factors can induce cartilage destruction. Interleukin-1 beta (IL-1β) is a potent pro-inflammatory cytokine that is capable of inducing chondrocytes and synovial cells to synthesize MMPs. The hypoxia-inducible factor-2alpha (HIF-2alpha, encoded by Epas1) is the catabolic transcription factor in the osteoarthritic process. The purpose of this study is to validate the effects of ecdysteroids (Ecd) on IL-1β- induced cartilage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
193
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(210 citation statements)
references
References 32 publications
15
193
2
Order By: Relevance
“…In folk, almost every part of T. sinensis , including seeds, bark, root bark, petioles, and leaves, can be used to treat cold, rheumatic pain, stomach pain, and diarrhea without any irreversible side effects [3, 4]. Modern pharmacological researches also demonstrated that this plant showed wide spectrum of biological activities, such as antioxidant [5], anti-diabetes [6], anti-inflammatory [7], antimicrobial [8], antinociceptive [9] and anti-tumor [10], due to its plentiful chemical constituents (limonoids, flavonoids, phytols, coumarins and norcyteine derivatives) [11–14]. …”
Section: Introductionmentioning
confidence: 99%
“…In folk, almost every part of T. sinensis , including seeds, bark, root bark, petioles, and leaves, can be used to treat cold, rheumatic pain, stomach pain, and diarrhea without any irreversible side effects [3, 4]. Modern pharmacological researches also demonstrated that this plant showed wide spectrum of biological activities, such as antioxidant [5], anti-diabetes [6], anti-inflammatory [7], antimicrobial [8], antinociceptive [9] and anti-tumor [10], due to its plentiful chemical constituents (limonoids, flavonoids, phytols, coumarins and norcyteine derivatives) [11–14]. …”
Section: Introductionmentioning
confidence: 99%
“…The current study is guided by an established sociobehavioral model of CHA[21-25], which is an extension of the Andersen Behavioral Model[26]. The original Andersen model posits utilization of conventional health care is a function of individuals’ predisposition to seek and use services, factors that aid or hinder access, medical need, and personal health practices[26].…”
Section: Introductionmentioning
confidence: 99%
“…The original Andersen model posits utilization of conventional health care is a function of individuals’ predisposition to seek and use services, factors that aid or hinder access, medical need, and personal health practices[26]. Our sociobehavioral model contends that CHA use is influenced by these four domains but is additionally motivated by health promotion and wellness behaviors[25,27]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations